IMPLEMENTASI DIGITAL MARKETING UNTUK OPTIMALISASI KINERJA UMKM SEKTOR MAKANAN & MINUMAN KOTA MEDAN - Rudianto Surbakti; Nurhaflah Soraya; Melvin Bismark Hamonangan Sitorus; Puan Shareenie Shera binti Abdul Hamid; Nik Rozilaini Wan Mohamed; Rini Indahwati (LPPI UMN AL WASHLIYAH, 2025)
Digital marketing known as a business strategic that mostly implemented in current business era, included small, medium enterprises, especially in the food & beverage sectors. For the community services activities, Politeknik Negeri Medan’s lecturers, colaborated with the lecturers form Universiti Teknologi Mara, Malaysia to implement the digital marketing at the Kafe Tenank in Kota Medan. This community service activity began with a presentation of material on digital marketing by the speaker and book author, followed by direct implementation of digital marketing. Community Services’ Team implemented the digital marketing process at the Kafe Tenank with the involvement of culinary influencer from Medan,Kulineran. Data that used in this digital marketing content were the location information, menu, prices of the products dan testimonies form the current customers of Kafe Tenank. The result of the community service’s activity was digital content that already published on social media of Medan.Kulineran collaborated with the social media of Kafe Tenank and also shared by the Politeknik Negeri Medan. The implementation of digital marketing expected to raise the number of visit the customers and potential customers. Furthermore, the digital content could be tools of branding for Kafe Tenank. At the end, the raise of customer’s visit will impact the revenue and income of the Kafe Tenank.